Cellulose hydrolysis and binding with Trichoderma reesei Cel5A and Cel7A and their core domains in ionic liquid solutions. Issue 4 (20th November 2013) - Wahlström, Ronny; Rahikainen, Jenni; Kruus, Kristiina; Suurnäkki, Anna
ABSTRACT Ionic liquids (ILs) dissolve lignocellulosic biomass and have a high potential as pretreatment prior to total enzymatic hydrolysis. ILs are, however, known to inactivate cellulases. In this article, enzymatic hydrolysis of microcrystalline cellulose (MCC) and enzyme binding onto the cellulosic substrate were studied in the presence of cellulose‐dissolving ILs. Two different ILs, 1, 3‐dimethylimidazolium dimethylphosphate ([DMIM]DMP) and 1‐ethyl‐3‐methylimidazolium acetate ([EMIM]AcO), and two monocomponent cellulases, Trichoderma reesei cellobiohydrolase Cel7A and endoglucanase Cel5A, were used in the study. The role and IL sensitivity of the carbohydrate‐binding module (CBM) were studied by performing hydrolysis and binding experiments with both the intact cellulases, and their respective core domains (CDs). Based on hydrolysis yields and substrate binding experiments for the intact enzymes and their CDs in the presence of ILs, the function of the CBM appeared to be very IL sensitive. Binding data suggested that the CBM was more important for the substrate binding of endoglucanase Cel5A than for the binding of cellobiohydrolase Cel7A. The CD of Cel7A was able to bind well to cellulose even without a CBM, whereas Cel5A CD had very low binding affinity. Hydrolysis also occurred with Cel5A CD even if this protein had very low binding affinity in all the studied matrices. Binding and hydrolysis were less affected by the studied ILs for Cel7A than for Cel5A. To our knowledge, this is the first systematic study of IL effects on cellulase substrate binding. Biotechnol. Bioeng. 2014;111: 726–733. © 2013 Wiley Periodicals, Inc.